2018
DOI: 10.1038/s41416-018-0125-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic immune profiling of ovarian cancers in paraneoplastic cerebellar degeneration associated with anti-Yo antibodies

Abstract: Our data pinpointed the enrichment of acquired immune response, particularly high density of CD8+ lymphocytes, and high-level expression of CDR-related antigens in anti-Yo PCD OT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 50 publications
(55 reference statements)
0
20
0
Order By: Relevance
“…High levels of CDR1 expression are observed in Purkinje cells and the interneurons of the cerebellar cortex (6,10). Transcriptomic pro ling showed higher CDR1 expression in ovarian tumours from PCD patients than in ovarian tumours from patients without PCD (12). We have shown that CDR1 is also expressed in breast and ovarian tumours in patients without PCD, but not in the corresponding healthy tissue (10).…”
Section: Introductionmentioning
confidence: 70%
“…High levels of CDR1 expression are observed in Purkinje cells and the interneurons of the cerebellar cortex (6,10). Transcriptomic pro ling showed higher CDR1 expression in ovarian tumours from PCD patients than in ovarian tumours from patients without PCD (12). We have shown that CDR1 is also expressed in breast and ovarian tumours in patients without PCD, but not in the corresponding healthy tissue (10).…”
Section: Introductionmentioning
confidence: 70%
“…Whether this expression is dependent on AIRE and whether it results in central T-cell tolerance remains unknown at this time. In this context, the observed up-regulation of AIRE mRNA expression in ovarian tumors associated with anti-Yo PCD as compared to other ovarian tumors is puzzling (114). Moreover, genes transcriptionally regulated by AIRE are enriched among those differentially expressed between anti-Yo-associated vs. control ovarian tumors, although the immunological consequences of this differential expression is unknown (114).…”
Section: Immune Tolerance and Pcdmentioning
confidence: 99%
“…In this context, the observed up-regulation of AIRE mRNA expression in ovarian tumors associated with anti-Yo PCD as compared to other ovarian tumors is puzzling (114). Moreover, genes transcriptionally regulated by AIRE are enriched among those differentially expressed between anti-Yo-associated vs. control ovarian tumors, although the immunological consequences of this differential expression is unknown (114). Protein involved in axon specification and outgrowth during early brain development and in the maintenance of microtubules.…”
Section: Immune Tolerance and Pcdmentioning
confidence: 99%
See 1 more Smart Citation
“…1 We have previously demonstrated, as has that same group, that anti-Yo antibodies are taken up by cerebellar Purkinje cells in rodent slice cultures and are able to cause neuronal death, possibly by interference with calcium signaling 2,3 The observations by Kråkenes et al correlate well with recent work demonstrating that ovarian tumors from anti-Yo-positive patients show high rates of genetic alterations in CDR2 and, to a greater extent, CDR2L Yo antigens, suggesting that tumor expression of one or both of these proteins may be a key event in breaking immunological tolerance and initiating Purkinje cell destruction. 4,5 We have two observations concerning Kråkenes et al's article. First, the work, although of high importance, does not actually demonstrate whether anti-CDR2L antibodies or anti-CDR2 antibodies are capable of causing Purkinje cell death.…”
mentioning
confidence: 96%